Node positivity in T1b gallbladder cancer: A high volume centre experience. Issue 7 (July 2022) - Goel, Mahesh; Pandrowala, Saneya; Patel, Prerak; Patkar, Shraddha
Abstract: Introduction: Identification of early stage gallbladder cancer (GBC) is difficult with simple cholecystectomy being considered curative for T1a GBC but T1b requires radical cholecystectomy due to chances of lymph node metastasis. However there is no consensus regarding the optimal treatment strategy for T1b disease. Methodology: A retrospective review of a prospectively maintained database of GBC patients operated at our institute from March 2010 to March 2021 was conducted. Only patients with proven gallbladder adenocarcinoma on final histopathology report were included. Results: A total of 1245 patients of suspected GBC who underwent surgery during this period with 76 patients of T1b stage were analysed. We divided the group into a node positive cohort (n = 16, 9 received neoadjuvant treatment due to uptake in periportal nodes and 7 patients were pN1) and a node negative cohort (n = 60). The median nodal harvest was 8 nodes (2–24 nodes). Considering the radiological and pathological parameters, the rate of lymph node positivity was 21% (16/76). The overall major morbidity was 5.2% and there was no mortality. After a median follow up of 47.5 months, 3-year OS and DFS of the node negative and positive cohort was 96.7%, 91.7% and 75% and 62.5% (p = 0.058). The node positive cohort had 43% recurrences whereas the node negative cohort had 8.3% with all recurrences limited to periportal lymph nodes, distant nodes or liver metastasis. Conclusion: Nodal positivity for T1b gall bladder cancer ranges around 21% and radical surgery with complete peri –portal lymphadenectomy should be considered as standard of care. Highlights: Node positivity in T1b gallbladder cancer is as high as 21%. Complete lymphadenectomy will upstage disease from Stage I to Stage III. Recurrence pattern predominantly periportal or distant without gallbladder fossa recurrence.